Polyethyleneimine-functionalized poly(methyl methacrylate) colloidal nanoparticles for directly coating natural rubber sheet - Panya Sunintaboon (2018)
This work illustrated a convenient surface modification of sulphur-prevulcanized natural rubber (SPNR) sheet with poly(methyl methacrylate) (PMMA) colloidal nanoparticles without pre-treatment of the rubber. The SPNR sheet was simply immersed into the latex of PMMA core that was functionalized with polyethyleneimine (PEI) shell (PMMA/PEI) via a soap-free emulsion polymerization. The presence of PMMA/PEI nanoparticles on the SPNR sheet was revealed by Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). It was also traced by the changes of surface roughness, adhesion force, and relative surface stiffness obtained from atomic force microscopy (AFM) analysis. The surface coverage (Cs) values depended on the variation of immersion time and particle concentration. Water contact angles on the PMMA/PEI-coated SPNR sheet decreased with increasing Csvalues. © 2009 Elsevier B.V. All rights reserved.